France : Selected Issues Paper. (IMF Staff Country Reports; Country Report, 2013)
This Selected Issues paper examines external developments and competitiveness in France. Over the past decade, the current account has deteriorated from a surplus of 1.2 percent of GDP in 2002 to a deficit of about 2.3 percent in 2012, as France lost ground in goods trade and services recorded just a slight increase in global market shares. The slight improvement of the trade deficit seen in 2012 may suggest a change in trend, although it is still too early to determine. Past deterioration in export performance points to competitiveness weaknesses, rooted in significant rigidities in labor and product markets.